KAJIAN KEBISINGAN DAN DAMPAKNYA TERHADAP MASYARAKAT DI JALAN BASUKI RAHMAT KABUPATEN TABALONG - Adi Rizani Rachman; Taufik Hidayat; Yohanes Joko S.; Andi Mizwar (Universitas Lambung Mangkurat, 2014)
This research has the purpose to know the relation among age variable, stay duration, distance between house and the road, house area , material of house wall, roof, ceiling/plafond, number of inhabitant, environment condition (patron tree), noise level about noise complaint. Analytical research method with design of Cross Sectional, implemented in three political district administration, they are Tanjung Subdistrict, Agung Subdistrict, and Hikun subdistrict. The result of research refers that there are relations among stay duration, distance between house and the road, environment condition (patron tree), traffic noise level about noise complaint for people. Patron tree and traffic noise level have a big contribution toward the complaint of people, they are easy to be angry, disturb a concentration in doing something, sleepless, disturb a rest if the door is opened. Concluded that the people in along of Basuki Rahmat street, Tanjung subdistrict, Tabalong regency have noise complaint cause of traffic.